Strategi Literasi Inklusif Mahasiswa Kukerta Tematik Universitas Riau Kelurahan Tembilahan Hulu : Lapak Literasi Dan Permainan Edukatif di Car Free Day - Chairul Chairul; Afriansyah Afriansyah; Bilqis Armadini Humairah; Feblin Isma Anjelika; Kamilyandri Kamilyandri; M. Fadli; Mildria Efitra; Muhammad Huday Alzuro; Nabila Rasya; Putri Maisalma; Tikkos Maruhum S.; Wahyu Sitorus; Zulfri Prio Anggoro (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Inclusive literacy stems from an awareness of the importance of equality and accessibility in education. This community service program was carried out by students from the University of Riau's Thematic Kukerta program, utilizing Car Free Day activities in Tembilahan Hulu as a public space to develop equitable access to literacy. The aim is for all children from diverse socio-economic backgrounds to have the opportunity to read, learn in an enjoyable manner, and boost their self-confidence through activities such as coloring contests without any discrimination. The methods employed include direct observation, participatory interaction, and the provision of reading materials and educational games. The results of the implementation showed an increase in children's and community enthusiasm for literacy activities in open spaces. Children's participation in reading activities increased significantly each week, and the relationship between students and the local TBM (Community Reading Garden) community grew stronger. This program not only expanded literacy access in public spaces but also provided an example of inclusive literacy strategies that can be adopted in other community service initiatives in the Indragiri Hilir region.